2021
DOI: 10.1111/bld.12364
|View full text |Cite
|
Sign up to set email alerts
|

Lost voices part 1: A narrative case study of two young men with learning disabilities disclosing experiences of sexual, emotional and physical abuse

Abstract: Accessible Summary Two young men who have learning disabilities were students at a college. While they were there, they were sexually abused by people who were meant to care for them. When they tried to tell people, some people would not listen. Some people listened but could not understand them. They became mentally ill because of the abuse. Then, some people started to listen and help them tell their stories. Then, the police and the courts said that the two young men could not give evidence in court becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Willott et al (2020) found that under reporting of sexual violence against people with a learning disability remains an on-going problem. Moreover, legal and safeguarding systems are often based on procedures that are inaccessible to adults with a learning disability (Digman, 2021), and prosecutions are uncommon and often unsuccessful (Murphy et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Willott et al (2020) found that under reporting of sexual violence against people with a learning disability remains an on-going problem. Moreover, legal and safeguarding systems are often based on procedures that are inaccessible to adults with a learning disability (Digman, 2021), and prosecutions are uncommon and often unsuccessful (Murphy et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the professional voice has been privileged in defining adult abuse and creating a regulatory framework in response, some, albeit limited, research has explored the perceptions of people with a learning disability who have experienced abuse (Eastgate et al, 2011;Leutar et al, 2014). Digman (2021) presents a narrative account of two male students, based in the UK, who experienced sexual, physical and emotional abuse, concluding that the perspective and experience of these victims, each of whom have a learning disability, often became lost within safeguarding processes. Digman identifies the need for victims, including those with profound communication issues, to have a voice in all matters relating to their safeguarding and care.…”
Section: Introductionmentioning
confidence: 99%
“…It details the therapeutic work, beginning with early response and covering 2 years of psychological interventions. The first paper describes the events prior to disclosure, the disclosures, the responses of professional agencies (legal, social care, mental health and education) and the immediate outcomes for the victims and their families (Digman, 2021). James and George were accommodated at college in the same Shared Lives provision with two people engaged as carers by an agency, S (female) and T (male).…”
Section: Introductionmentioning
confidence: 99%